Post-acute coronavirus disease 2019 (COVID 19) syndrome: HLH and cholangiopathy in a lung transplant recipient. (July 2022) - Roda, Silvia; Ricciardi, Alessandra; Maria Di Matteo, Angela; Zecca, Marco; Morbini, Patrizia; Vecchia, Marco; Chiara Pieri, Teresa; Giordani, Paola; Tavano, Angelo; Bruno, Raffaele
Highlights: In COVID19-associated respiratory failure, lung transplantation might be an option; Sars-CoV2 infection was recognized as a cause of HLH in severe COVID19 cases; Post-Covid cholangiopathy is described as a new clinical entity; The treatments for HLH can increase the risk of infection of transplant recipients. Abstract: Background: Sars-CoV2 can cause severe pneumonia and acute respiratory distress syndrome (ARDS). In COVID-19-associated respiratory failure, lung transplantation might be an option (Bharat A). Case report: A previously healthy 63-year-old man with a nasopharyngeal swab positive for SarsCoV2 and radiological evidence of interstitial lung consolidations developed acute respiratory distress that required intubation and veno-venous extracorporeal membrane oxygenation support (VV ECMO). Because of no recovery of his lung function, he underwent a bilateral lung transplant. ICU stay was complicated by several episodes of bacterial superinfections and an increase of liver function tests (LFTs). Afterward, he faced a progressive clinical worsening associated to severe anemia, further rise of indices of cholestasis, hypertriglyceridemia and hyperferritinemia. Bone marrow smear showed a picture compatible with haemophagocytic lymphohistocytosis (HLH) and first and second line therapy were started. In addition, a transjugular hepatic biopsy was performed with histopathological evidence of portal and periportal fibrosis, compatible with Covid 19-related cholangiopathy. During the hospital stay, he developed several MDR opportunistic infections. The patient died few months later from multiorgan failure secondary to septic shock. A post-mortem confirmed a diagnosis of cholangiopathy, and medullary erythro -haemophagocytosis. Conclusion: Post Covid19 syndrome is a clinical entity that includes novel and old sequelae following recovery from Sars-CoV2 infections. Early identification of these diseases is crucial for adequate management and might influence the long term prognosis of these patients.